2020
DOI: 10.1103/physrevd.101.055007
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous anomalies from virtual black holes

Abstract: We investigate gravitational UV/IR mixing models that predict a breakdown of low energy effective field theory, from loop-level, non-local gravitational corrections to particle processes. We determine how the choice of IR cutoff in these theories alters predictions for lepton magnetic moments. Using Brookhaven E821 muon magnetic moment data, we exclude models of UV/IR mixing with an IR cutoff set by a spherical volume enclosing the experiment. On the other hand, an IR cutoff defined by the simply-connected spa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…However, this only applies if the other method we propose works anyway (i.e when the modular Hamiltonian is local) and would be much more difficult. 7 There actually is small error in Casini and Huerta's result: a missing boundary term in equation 7. We did not exposit on it here for space and because the missing term does not affect our final result.…”
Section: The Spectrum Of the Vacuum Skewed Correlation Matrix Via A L...mentioning
confidence: 90%
See 2 more Smart Citations
“…However, this only applies if the other method we propose works anyway (i.e when the modular Hamiltonian is local) and would be much more difficult. 7 There actually is small error in Casini and Huerta's result: a missing boundary term in equation 7. We did not exposit on it here for space and because the missing term does not affect our final result.…”
Section: The Spectrum Of the Vacuum Skewed Correlation Matrix Via A L...mentioning
confidence: 90%
“…Casini and Huerta studied the entropy of an n-sphere in a scalar vacuum and among their work they give the explicit formula for the modular Hamiltonian of this state [24]. Comparing equations 7 and 8 in Casini and Huerta's work 7 with our formula for the Modular Hamiltonian in equation (3.10) and defining p(r) = 1 − r 2 we get an expression for h ′ (α 0,Ω,d ) as a differential operator operating on two components ϕ 1 and ϕ 2 of a vector in C.…”
Section: The Spectrum Of the Vacuum Skewed Correlation Matrix Via A L...mentioning
confidence: 99%
See 1 more Smart Citation
“…CKN calculated the minimum possible correction to the electron g − 2 by simultaneously varying both UV and IR cutoffs [2]. On the other hand, in a companion paper [6], we have found that a straightforward choice for the infrared cutoff Λ IR , leads to interesting and measurable consequences for the muon g − 2. Indeed, we have found that this could serve as an explanation of the anomalous muon g − 2 anomaly observed in the last decade.…”
Section: Experimental Consequences For Matter Effect Uv/ir Mix-ingmentioning
confidence: 93%
“…We see that the precision measurements of lepton magnetic moment required to test matter effect gravitational UV/IR mixing lie beyond present experimental capabilities. However, this matter effect would be sought after first finding a larger vacuum gravitational UV/IR mixing effect, which could be found at current experiments [6].…”
Section: Experimental Consequences For Matter Effect Uv/ir Mix-ingmentioning
confidence: 96%